PENANGGULANGAN KEJAHATAN PEROMPAKAN LAUT DI INDONESIA BERDASARKAN PERSPEKTIF HUKUM PIDANA INTERNASIONAL - Kurniasanti Kurniasanti; Joko Setiyono (STIH Putri Maharaja, 2020)
The crime of piracy at sea is one of the acts of violence or illegal detention, or any act of destruction committed for personal purposes by the crew of a ship or a passenger of a private ship or aircraft and aimed at the high seas, against other ships or aircraft or against persons or goods that are on board a ship or aircraft somewhere outside the jurisdiction of any country. This article aims to analyze the implementation of the universal jurisdiction of a country in tackling the crime of marine piracy in Indonesia and the preventive measures applied by the government in protecting Indonesian-flagged ships in foreign territorial waters that are prone to armed robbery. This research uses doctrinal legal research. Doctrinal legal research is research on law that is conceptualized and developed on the basis of the doctrine adhered to by the conceptor and / or the developer. Sources of legal information use primary legal materials (regulations and relevant documents) for further qualitative analysis. The approach used is statutory, conceptual, and analysis to help solve the problem formulation. Piracy is a common enemy of the international community which has tremendous consequences for international security. Regarding prosecuting perpetrators of piracy crimes, in this case international law itself has transferred its powers to all countries, namely the application of the principle of universal jurisdiction.